Modelling of DC shipboard power system - Satpathi, Kuntal (2019)
Modelling and simulation of emerging DC shipboard power system (SPS) is required to validate the hardware design, converter control and protection algorithms. As DC SPSs may be large and complicated, the simulation of such systems using high fidelity models generally consumes much time and the validation of performance using multiple test scenarios becomes impractical. An alternative method is to conduct such simulations in real-time using a multi-core simulation platform. Real-time simulation also allows protection relays (running embedded protection algorithms) to be verified through `hardware in the loop' techniques. In this paper we discuss the simulation of DC SPSs in real-time using Opal-RT simulation platform. Firstly the system is modelled for non-real-time simulation. Subsequently these models are converted for real-time simulation and executed using RT-Lab on the Opal-RT target. Modelling and control approaches of DC SPS and some of the attributes of Opal-RT are also discussed.